Artistic Orientation, Financial Literacy, Digital Literacy, and MSME Performance - Ifah Rofiqoh (Program Studi S3 Ilmu Manajemen, 2023)
The limitations of research linking artistic orientation with performance motivate researchers to examine artistic orientation in creative MSMEs. Their uniqueness is that they combine art and economics, resulting in original creations and the ability to compete and succeed in the market. To combine these two things, a performance improvement strategy is needed, among others by increasing literacy. This study examines whether managers perform better artistically and whether financial and digital literacy affects performance. This study uses primary data from questionnaires to 344 creative MSMEs in Yogyakarta. Data analysis using Partial Least Square - SEM results show that artistic orientation has a significant effect on non-financial and financial performance. Financial literacy and digital literacy have a significant effect on financial performance.